2023
DOI: 10.1177/19458924231210028
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Chronic Rhinosinusitis and Reflux Diseases in Adults: A Systematic Review and Meta-Analysis

Ahmad Aldajani,
Fahad Alhussain,
Tamer Mesallam
et al.

Abstract: Background Over the last few decades, reflux diseases, such as laryngopharyngeal reflux (LPR) and gastroesophageal reflux disease (GERD), have been identified as significant contributors to inflammatory upper aerodigestive tract diseases. Establishing a direct relationship between reflux disease and chronic rhinosinusitis (CRS) is challenging due to the high prevalence of both diseases and their potential for independent coexistence. Objective The purpose of this study is to review the existing literature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Aldajani and colleagues conducted a meta-analysis assessing the association between reflux diseases (laryngopharyngeal reflux [LPR] and gastroesophageal reflux [GERD]) and CRS. 6 The study revealed a significant association between GERD, LPR, and CRS compared to control groups, along with higher pH values and pepsin detection in CRS patients. Additionally, studies evaluating proton inhibitor therapy in CRS patients consistently reported positive outcomes.…”
mentioning
confidence: 74%
“…Aldajani and colleagues conducted a meta-analysis assessing the association between reflux diseases (laryngopharyngeal reflux [LPR] and gastroesophageal reflux [GERD]) and CRS. 6 The study revealed a significant association between GERD, LPR, and CRS compared to control groups, along with higher pH values and pepsin detection in CRS patients. Additionally, studies evaluating proton inhibitor therapy in CRS patients consistently reported positive outcomes.…”
mentioning
confidence: 74%